Institutional Decoupling in Archipelagic Logistics: Why Global Standards Do Not Strengthen Digital Policy Effectiveness in Indonesia - Ibnu Romadhona; Rully Indrawan; Euis Saribanon; Siti Maemunah (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: As an archipelagic nation, Indonesia faces complex logistics challenges, including limited connectivity, infrastructure disparities, and high inter regional distribution costs. In response, the government and industry stakeholders have adopted various global best practices in digital logistics transformation, yet their implementation often fails to produce the expected outcomes. Objective: This study analyses the effect of National Logistics Ecosystem (NLE) policy implementation on logistics service performance, with digitalization, digital ecosystem maturity, and openness to global best practices as moderating variables, and explains why openness to global best practices does not strengthen that effect. Methods: The study employed a mixed-methods approach with an explanatory sequential design. Quantitative data from 388 respondents were analyzed using SmartPLS 4 and NVivo 14. Results: NLE policy implementation positively and significantly affects logistics service performance, and this effect is strengthened by digitalization and digital ecosystem maturity. In contrast, openness to global best practices neither moderates the relationship nor exerts a significant direct effect on performance. Qualitative analysis attributes this dual null result to Institutional Decoupling, whereby international standards are formally adopted without operational internalization, driven by inter agency sectoral fragmentation and pronounced infrastructure disparities between western and eastern Indonesia, and compounded by uneven digital literacy and conservative organizational cultures. Conclusion: These findings indicate that, absent foundational domestic harmonization, international standards remain ceremonial and lose operational relevance. A sequenced, domestic first approach is therefore required, one that couples regulatory measures to dismantle sectoral silos with investment in digital literacy and human resource capacity.